حديث خلق العناصر الأربعة: دلالاته العرفانية والخلقية وأبعاده العلمية - Al-Khayrabadi, Mohammed Abul Lais (IIUM, 2016)
مستخلص البحث ﻫــﺬا المقـﺎل ﳏﺎوﻟــﺔ ﻟــﺸﺮح ﺣــﺪﻳﺚ ﺧﻠــﻖ اﻟﻌﻨﺎﺻــﺮ اﻷرﺑﻌــﺔ: اﻟــﱰاب، واﻟﻨــﺎر، واﳌــﺎء، واﳍــﻮاء، وﻟﻠﺘﺄﻣﻞ ﰲ اﻷﺑﻌﺎد اﻟﻌﻠﻤﻴﺔ، وذﻟﻚ ﻣﻦ ﺧﻼل اﻟﻨﻈﺮ ﰲ ﺧﺼﺎﺋﺺ ﺗﻠﻚ اﻟﻌﻨﺎﺻﺮ ﻣـﻦ ﺣﻴـﺚ اﻟﻘﻮة واﻟﻀﻌﻒ واﻟﻠﻄﺎﻓﺔ واﻟﻜﺜﺎﻓـﺔ، وﻣـﻦ ﺧـﻼل اﻟﺘﻔﻜـﺮ ﰲ ﻋﻼﻗـﺔ ﺑﻌـﻀﻬﺎ ﺑـﺒﻌﺾ ﻣـﻦ ﻧﺎﺣﻴـﺔ ﺗﺮﺗﻴﺒﻬـــﺎ اﻟﻄﺒﻴﻌـــﻲ وأﺛـــﺮ ﺑﻌـــﻀﻬﺎ ﰲ ﺑﻌـــﺾ. وأﻫـــﻢ ﻣـــﻦ ذﻟـــﻚ ﻳﻨﻈـــﺮ اﳌﻘـــﺎل ﰲ اﳌﻌـــﺎﱐ اﻟﺮوﺣﻴـــﺔ واﻟــﺪﻻﻻت اﻟﻌﺮﻓﺎﻧﻴــﺔ واﳋﻠﻘﻴــﺔ اﻟــﱵ ﻳﻨﻄــﻮي ﻋﻠﻴﻬــﺎ اﳊــﺪﻳﺚ، وﻳــﺴﻌﻰ إﱃ اﻟﺘﺒــﺼﺮ ﺑﺂﺛــﺎر ﺗﻠــﻚ اﳌﻌـﺎﱐ واﻟـﺪﻻﻻت ﺑﺎﻟﻨـﺴﺒﺔ ﳊﻴـﺎة اﻹﻧـﺴﺎن وﺳـﻠﻮﻛﻪ وﻋﻼﻗﺎﺗـﻪ، وﺧﺎﺻـﺔ ﻣـﻦﻣﻘـﺎم ﻋﺒﻮدﻳﺘــﻪ ﷲ ﺗﻌﺎﱃ وﺗﺼﺮﻓﻪ ﰲ أﺷﻴﺎء اﻟﻌﺎﱂ اﻟﱵ ﺟﻌﻠﺖ ﻣﺴﺨﺮة ﻟﻪ. اﻟﻜﻠﻤﺎت اﻷﺳﺎﺳﻴﺔ:اﻟﻌﻨﺎﺻﺮ اﻷرﺑﻌﺔ، اﻟﻠﻄﺎﻓﺔ، اﻟﻜﺜﺎﻓﺔ، اﻟﺮوح، اﻟﻌﺒﻮدﻳﺔ، اﻟﻌﺮﻓﺎن، اﻷﺧﻼق، اﻟﻔﻀﺎﺋﻞ. Abstract This article is an attempt to comment on the Prophetic tradition on the creation of the four elements (sand, fire, water and air) and to reflect on its scientific connotations by looking into the characteristics of those elements in terms of strength and weakness as well as density and fineness. It also ponders on their relationships with one another in accordance with their natural order and their effect on each other. More importantly, the article reflects on the spiritual meanings and Gnostic denotations and ethical implications of the Hadith. This is done with the purpose of thinking out the consequences of those denotations and implications for man’s life, conduct and relations, especially in relations to his status of servitude to God Almighty and his authority to dispose of the things that have been made subservient to him in this world. Keywords:The four elements, science, morality, virtues, servitude.